2009
DOI: 10.1098/rspb.2009.1515
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of swim speed and stroke frequency in geometrically similar penguins: they swim optimally to minimize cost of transport

Abstract: It has been predicted that geometrically similar animals would swim at the same speed with stroke frequency scaling with mass 21/3 . In the present study, morphological and behavioural data obtained from free-ranging penguins (seven species) were compared. Morphological measurements support the geometrical similarity. However, cruising speeds of 1.8-2.3 m s 21 were significantly related to mass 0.08 and stroke frequencies were proportional to mass 20.29 . These scaling relationships do not agree with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
111
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(128 citation statements)
references
References 28 publications
14
111
0
1
Order By: Relevance
“…By contrast, during ascent, negatively buoyant seals employed active stroking (high ascent strokes-per-metre) more than prolonged gliding (figure 2). Seals appeared to adjust stroking effort depending on buoyancy changes to maintain a narrow range of ascent swim speeds (figure 2; electronic supplementary material, figure S4), which might reflect a swim speed that minimizes swimming costs in the buoyancy-hindered direction [25,45,46].…”
Section: Discussion (A) Buoyancy Determines Locomotor Costs Of Swimmingmentioning
confidence: 99%
“…By contrast, during ascent, negatively buoyant seals employed active stroking (high ascent strokes-per-metre) more than prolonged gliding (figure 2). Seals appeared to adjust stroking effort depending on buoyancy changes to maintain a narrow range of ascent swim speeds (figure 2; electronic supplementary material, figure S4), which might reflect a swim speed that minimizes swimming costs in the buoyancy-hindered direction [25,45,46].…”
Section: Discussion (A) Buoyancy Determines Locomotor Costs Of Swimmingmentioning
confidence: 99%
“…If we replace the spring constant with muscle stiffness, we would expect the frequency of oscillatory movements in animals to increase with increasing muscle stiffness and decrease with increasing body mass. Much work on oscillatory movement has shown that body size is often correlated with frequency (Heglund and Taylor, 1988;Young et al, 1992;Lindstedt and Schaeffer, 2002 and references therein; Hurlbert et al, 2008;Sato et al, 2010;Dickerson et al, 2012). The frequency of muscle activation during shivering thermogenesis also seems to be correlated with body mass (Spaan and Klussmann, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…For both pelagic marine animals and AUVs it is common to transit at or near U opt minimising the COT and in the case of AUVs maximising the range, Sato et al (2010). Figure 9 compares the optimum cost of transport, COT opt , for various marine animals and AUVs.…”
Section: Optimum Cost Of Transportmentioning
confidence: 99%